ظاهرة الخلافية الفروعية في إندونيسيا: الأثر والحل من منظور الدعوة - Muhammad Ridwan Yahya; Siti Nuri Nurhaidah; Usman Umar; Haris Hakam (Al-Risalah : Jurnal Studi Agama dan Pemikiran Islam, 2024)
ظاهرة الخلافية الفروعية في إندونيسيا هي حدث مثير للجدل ينطوي على اختلافات في الرأي حول قضايا ثانوية أو فروع الدين. ويختلف تأثير هذه الظاهرة اختلافا كبيرا، بدءا من استقطاب المجتمع إلى انقسام الطوائف الدينية. ومنظور الدعوة في التغلب على هذه الظاهرة هو تعزيز التعليم الديني الذي يعزز الفهم الصحيح والتسامح مع الاختلافات. وثمة حل آخر يتمثل في زيادة الوعي بأهمية الحوار بين الأديان لتحقيق التفاهم المشترك. بالإضافة إلى أهمية دور العلماء والقيادات الدينية في تقديم التوجيه الصحيح لشعوبهم حتى لا يقعوا في الخلافية الفروعية. وبالتالي، يؤمل أن يتمكن المجتمع من الحفاظ على التكاتف واحترام الاختلافات في الرأي من أجل التنوع المتناغم في إطار الوحدة الوطنية The phenomenon of khilafiyah furuiyah in Indonesia is a controversial event involving differences of opinion on minor or furu' (branch) matters of religion. The impacts of this phenomenon are diverse, ranging from societal polarization to the fragmentation of religious communities. From the perspective of dakwah (Islamic outreach), addressing this phenomenon involves strengthening religious education that emphasizes correct understanding and tolerance of differences. Another solution is to raise awareness of the importance of interfaith dialogue to achieve mutual understanding. Additionally, the role of scholars and religious leaders in providing proper guidance to their followers to avoid falling into khilafiyah furuiyah is crucial. Thus, it is hoped that the society can maintain unity and respect differences of opinion for the sake of harmonious diversity within the framework of national unity